2016
DOI: 10.1177/0308022615621567
|View full text |Cite
|
Sign up to set email alerts
|

The journey of young people in an early psychosis program involved in participatory photography

Abstract: Introduction: The purpose of this study was to examine the experiences and perceptions of young people in an early psychosis program towards participating in a 10-week photovoice and exhibition project and the themes that had emerged from their photographs. Method: Photographs create meanings and participants are able to tell their stories in a meaningful way. Eleven clients who had gone through a prior 10-week photovoice project and exhibition consented to being interviewed for this study. Clients chose and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 24 publications
0
28
0
3
Order By: Relevance
“…For Jose, this was realising that things were going better for him than he thought (Padgett, Smith, Derejko, Henwood, & Tiderington, ). In the other four studies, increased self‐understanding was reported (Maniam et al, ; Reid & Alonso, ; Sitvast et al, ; Sitvast & Abma ; Sitvast ; Tang, Tse, & Davidson, ). For example, in Reid and Alonso (), one participant said they were “surprised how much of my internal struggles and thought processes came out through the pictures.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…For Jose, this was realising that things were going better for him than he thought (Padgett, Smith, Derejko, Henwood, & Tiderington, ). In the other four studies, increased self‐understanding was reported (Maniam et al, ; Reid & Alonso, ; Sitvast et al, ; Sitvast & Abma ; Sitvast ; Tang, Tse, & Davidson, ). For example, in Reid and Alonso (), one participant said they were “surprised how much of my internal struggles and thought processes came out through the pictures.…”
Section: Resultsmentioning
confidence: 91%
“…Four studies reported that PP had empowered participants (Maniam, Kumaran, Ping‐Lee, Koh & Subramaniam, ; Reid & Alonso, ; Rolbiecki, Anderson, Teti & Albright, ; Sitvast ; Sitvast & Abma ; Sitvast, Abma, & Widdershoven, ). This section is divided into the two sub‐themes of personal empowerment and empowerment through exhibitions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations